Economics and Crime Rates in Indonesia - Rahman, Yozi Aulia; Prasetyo, Affandi Dwi (Universitas Negeri Semarang, 2018)
The Indonesian economy indicates good performance but it is not followed by the decrease in crime rates. The aim of research is to find out and analyze the effects of unemployment, education, wages, and case completion rates on the crime rates in Indonesia in 2012 – 2016. This research uses the panel data using the Fixed Effect Model (FEM) with Generalized Least Square (GLS) method. The data used in this research is the secondary data collected from the Central Bureau of Statistics and the Indonesian National Police since 2012 until 2016. The data includes the open unemployment rate, the school enrollment rates, the provincial minimum wages, the crime rates, and the case completion rates. The result of this research indicates that the variables of unemployment, education and case completion rates insignificantly affect on the criminal crime in Indonesia. The wages have negative and significant effect on the crime rates in Indonesia.